Fault Reconstruction for a Quadrotor Using an LPV Sliding Mode Observer1. Issue 21 (2015) - Chandra, Kumar Pakki Bharani; Alwi, Halim; Edwards, Christopher
Abstract: This paper deals with actuator fault reconstruction in an uncertain quadrotor using a linear parameter varying (LPV) sliding mode observer. First an LPV model of a quadrotor is presented and then an LPV sliding mode observer is developed to reconstruct faults in the actuators. Unlike many existing LPV fault detection schemes for quadrotors, in this paper the measured LPV scheduling parameter is also allowed to potentially be faulty. The main focus of this paper is to detect actuator faults in the motors of an uncertain quadrotor with inaccurate scheduling parameters using a sliding mode observer. Simulations are performed on the full nonlinear model to show the efficacy of the LPV sliding mode observer in reconstructing the faults.